PENGUASAAN KOSAKATA BAHASA INGGRIS PADA MAHASISWA D3 TEKNIK SIPIL UNIVERSITAS DIPONEGORO SEMARANG - Wiwiek Sundari (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2014)
This research is aimed at knowing the mastery of English vocabulary of the 2010 D3 of Civil Engineering student of Diponegoro University. To research the objective, the researcher has observedthe sum of 30 respondents by giving them tests and questionares to collect data. The tests and questionares include productive and receptive vocabulary. The collected data are grouped andanalyzed based on their kids (such as nouns, verbs, adjectives, adverbs, and function words) and they are also analyzed in terms of their usage in various constractions, such as in phrase, clauses, andsentences.